Review of Sharia Economic Law on Peer-to-Peer Lending Practices Based on DSN-MUI Fatwa and Opinions of Contemporary Scholars - Ubaidillah; Alfianto; Nurjannah, Feby; Arifin, Mohammad Samsul (Tasyri' : Journal of Islamic Law, 2026)
The development of the fintech industry, especially the peer to peer (P2P) lending model, is growing very rapidly in Indonesia. Peer to-Peer (P2P) Lending is a mechanism to raise funds through a platform or fintech company, which is then distributed to business actors in the form of loans. This study aims to analyze the practice of peer to peer (P2P) lending in accordance with the fatwa of DSN-MUI No. 117/DSN-MUI/II/2018 and contemporary scholars. This study uses a type of library research and a normative approach with data collection techniques in the form of documentation, while the validity of the data is tested through source triangulation. The results of this study show that the DSN-MUI Fatwa No. 117/DSN-MUI/II/2018 and the views of contemporary scholars affirm that P2P lending is allowed as long as it is in accordance with sharia principles, free of usury, gharar, and maysir, and uses a valid contract under the supervision of the Sharia Supervisory Board (DPS).